Effectiveness of Edpuzzle Interactive Video on Student Interest and Learning Outcomes - Zakiyyah, Amirah Qonitatus; Surahman, Ence; Fadhli, Muhibuddin; Thaariq, Zahid Zufar At (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: This research was carried out due to the low level of student interest and learning outcomes in the historical material on the Japanese occupation period, caused by the complexity of the subject matter and the limited use of interactive and engaging learning media. And in previous research, it was still rare to examine the use of Edpuzzle in social studies, especially in history material, where previous research mostly examined science or mathematics.Purpose: The research was employed to determine the effectiveness of Edpuzzle interactive video learning media on students’ interest and learning outcomes in the topic of the Japanese occupation period for eighth-grade junior high school students.Method: This research employed a quantitative approach by a quasi-experimental design, specifically utilizing the non-equivalent pre-test post-test control group design.Results: The outcomes revealed that the use of Edpuzzle media was effective in improving students’ learning interest, but was not yet sufficiently effective in enhancing students’ learning outcomes on the topic of the Japanese occupation period for eighth-grade junior high school students. Where students’ interest in learning increased to 82.70% after using Edpuzzle.Theoretical implication: This research strengthens the CTML theory that reveals that interactive media can improve the learning process.Practical implication: The outcome of this research can be used to decide appropriate learning media for students.